PERAN PENYULUH PERTANIAN DALAM PELESTARIAN ALAM - Nugroho, Tri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
This article aims to answer on what is the agriculture extention workers role in the environmental revitalization. The library research using an analytical-critical method showed that the agriculture extention workers role should be able to change communities behaviors to be more responsible for what they will do, proactive, future oriented, and respectful to the local wisdoms.